CAGE13-4 Cruise Report: Sub-seabed CO2 Storage: Impact on Marine Ecosystems (ECO2) (A 7th Framework Programme EU project) PART II. - Bünz, Stefan (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
Cruise CAGE 13-4 focused on the acquisition of acoustic data in two of the main target areas within CAGE, the deep (>1000 m water depth) seeping Vestnesa Ridge area and the shallower (< 400 m) highly active Prins-Karls Foreland (PKF) sites. Scientific problems that are to be addressed in these two key target areas include the periodicity of seepage (i.e. time scales of active, inactive and reactivated systems), quantification of gas and hydrates, the nature of gas sources, trigger mechanisms for seepage and the architecture of the fluid flow structures underlying seafloor seepage sites. Specific objectives of the cruise were as follows: To repeat a P-cable survey covering the active seeps on the Vestnesa Ridge in order to develop time-lapse 4D seismic studies of gas leakage. To acquire a P-cable survey at the active seeping area offshore PKF for planning and re-evaluation of drilling sites during the upcoming MeBo cruise in 2014. To repeat hydro-acoustic surveying for monitoring of flares in PKF active area. The cruise may be known as: CAGE13_7_ECO2_II